BEDMAP3 - Ice thickness, bed and surface elevation for Antarctica - standardised data points - Alan Aitken (Contact); Alan Aitken (Creator); School of Earth and Oceans (isManagedBy)
External Organisations British Antarctic Survey; University of Bristol; Columbia University; Istituto Nazionale Di Geofisica E Vulcanologia; University of Edinburgh; University of Texas; Centro de Estudios Cientificos; University of Washington; Polar Research Institute of China; Universität Bremen; Federal Institute for Geosciences and Natural Resources; University of Tübingen; University of Alabama; Stockholm University; Amherst College; University of Arizona; St. Olaf College; Northumbria University; Norwegian Polar Institute; University of Oslo; University of Kansas; NASA Goddard Space Flight Center; Stanford University; Dartmouth College; Western Norway University of Applied Sciences; University of York; University of Tasmania; Newcastle University; Imperial College London; Alfred Wegener Institute - Helmholtz Centre for Polar and Marine Research; California Institute of Technology; Technical University of Denmark; National Centre for Polar and Ocean Research, Ministry of Earth Sciences; Research Organization of Information and Systems, National Institute of Polar Research; National Aeronautics and Space Administration; Korea Polar Research Institute; All Russian Geological Research Institute; University of Brussels; University of California Santa Barbara; University of California Irvine; University of California San Francisco Associated Persons Alice Fremand (Creator); Peter Fretwell (Creator); Julien Bodart (Creator); Hamish Pritchard (Creator); Jonathan Bamber (Creator); R.E. Bell (Creator); C Bianchi (Creator); Robert Bingham (Creator); Donald Blankenship (Creator); G. Casassa (Creator); Ginny Catania (Creator); K Christianson (Creator); H Conway (Creator); Hugh Corr (Creator); X. Cui (Creator); D Damaske (Creator); V. Damn (Creator); R. Drews (Creator); G. Eagles (Creator); O. Eisen (Creator); H. Eisermann (Creator); Fausto Ferraccioli (Creator); Rene Forsberg (Creator); S Franke (Creator); S. Fujita (Creator); Y. Gim (Creator); V. Goel (Creator); P. Gogineni (Creator); J.S. Greenbaum (Creator); B. ...